Plasma Vitamin C Concentrations and Cognitive Function: A Cross-Sectional Study - Travica, Nikolaj; Ried, Karin; Sali, Avni; Hudson, Irene; Scholey, Andrew; Pipingas, Andrew (Frontiers in Aging Neuroscience, 2019)
Vitamin-C is a water soluble molecule that humans have lost the ability to produce. Vitamin-C plays a role in CNS functions such as neuronal differentiation, maturation, myelin formation and modulation of the catecholaminergic systems. A recent systematic review by our team indicated the need for further research into the relationship between plasma vitamin C and cognition in cognitively intact participants using plasma vitamin C concentrations instead of estimates derived from food-frequency-questionnaires (FFQ), and more sensitive cognitive assessments suitable for cognitive abilities vulnerable to aging. It was hypothesized that higher plasma vitamin C concentrations would be linked with higher cognitive performance. This cross-sectional trial was conducted on healthy adults (n=80, Female= 52, Male=28, 24-96 years) with a range of plasma Vitamin C concentrations. Cognitive assessments included The Swinburne-University-Computerized-Cognitive-Assessment-Battery (SUCCAB) and two pen and paper tests, the Symbol-Digits-Modalities-Test (SDMT) and Hopkins-Verbal-Learning-Test-Revised (HVLT-R). The pen and paper assessments were conducted to establish whether their scores would correlate with the computerized tasks. Plasma-Vitamin C concentrations were measured using two biochemical analyses. Participants were grouped into those with plasma vitamin-C concentrations of adequate level (≥28μmol/L) and deficient level (<28μmol/L). The SUCCAB identified a significantly higher performance ratio (accuracy/reaction-time) in the group with adequate vitamin-C levels vs deficient vitamin-C on the choice reaction time (M=188±4 vs167±9, p=0.039), immediate recognition memory (M=81±3 vs 68±6,p=0.03), congruent Stroop (M=134±3 vs 116±7, p=0.024), and delayed recognition tasks (M=72±2 vs 62±4, p=0.049), after adjusting for age (p<0.05). Significantly higher scores in immediate recall on the HVLT-R (M=10.64±0.16 vs 9.17±0.37, p=0.001), delayed recall (M=9.74±0.22 vs 7.64±0.51, p<0.001), total recall (M=27.93±0.48 vs 24.19±1.11, p=0.003) were shown in participants with adequate plasma Vitamin-C concentrations, after adjusting for vitamin-C supplementation dose (p<0.05). Similarly, higher SDMT scores were observed in participants with adequate plasma Vitamin-C concentrations (M=49.73±10.34 vs 41.38±5.06, p=0.039), after adjusting for age (p<0.05). In conclusion there was a significant association between vitamin-C plasma concentrations and performance on tasks involving attention, focus, working memory, decision speed, delayed and total recall, and recognition. Plasma vitamin C concentrations obtained through vitamin C supplementation did not affect cognitive performance differently to adequate concentrations obtained through dietary intake.